S19 Increased CRTH2 expression in asthmatic bronchial epithelium. (14th November 2013) - Johal, K; Southworth, T; Plumb, J; Singh, D
Abstract : Introduction and Objectives: Prostaglandin-D2 (PGD2) mediates chemotaxis of Th2 cells, basophils and eosinophils through the chemoattractant receptor homologous-molecule expressed on T-helper-type-2 cells (CRTh2). Pulmonary PGD2 levels are increased in patients with more severe asthma and higher levels of Th2 inflammation. CRTh2 antagonists, designed to block PDG2 signalling, are in clinical development for the treatment of asthma. We investigated whether pulmonary CRTh2 expression is upregulated in patients with asthma compared to controls; we focused on the bronchial epithelium and cells within the submucosa. Methods: Bronchial biopsies were obtained from asthmatic patients (n = 20) and healthy subjects (n = 10). Sections were probed with an anti-human CRTh2 antibody, a secondary biotinylated goat anti-rabbit antibody and the position of the CRTh2 receptors were visualised with 3, 3'-Diaminobenzidine (DAB) and counter-staining with haemotoxylin. Digital micrographs were taken and analysed using the ImageProPlus 6.0 software. The percentage positive area of epithelium was calculated along with the intensity of staining. These values were multiplied together to give an overall immunohistochemical (IHC) score for each subject. The number of positive cells/mm 2 within the submucosa was also counted. Results: CRTh2 expression was predominantly within the epithelium rather than the submucosa. There was a statistically significant (p = 0.04) increase the immunohistochemical score in the epithelium of asthmatics (74.7) compared to healthy non-smokers (38.8). There was no significant difference (p = 0.64) in the number of positive cells expressing CRTh2 within the submucosa between asthma patients (473/mm 2 ) and healthy controls (353/mm 2 ). Conclusion: CRTh2 expression is upregulated in the epithelium of asthmatic patients compared to healthy controls. This is a novel finding, suggesting that CRTh2 antagonists may exert therapeutic effects on the bronchial epithelium as well as blocking inflammatory cell chemotaxis in asthma.